FILSAFAT ILMU DALAM PENGEMBANGAN ILMU PENGETAHUAN - Sudur; Ahmad Syukri; Badarussyamsi (Jurnal Genta Mulia, 2024)
Philosophy is a science that is extensive, meaning that it is closely related to our daily lives. In fact, it can be said that philosophy is the driving force of our daily lives as individuals and as collective human beings in the form of a society or nation. chroPhilosophy of science is a philosophical reflection of the nature of science that will not recognize a stopping point in the direction of the goals to be achieved, namely truth and reality. Understanding the philosophy of science means understanding the intricacies of science so that the most basic aspects and joints, to understand the perspective of science, the possibility of its development, and the interrelationships between branches of science with one another. The research approach that researchers use in writing scientific papers is a type of library research. It can be concluded that philosophy is a science that studies seriously the nature of the truth of all things. Science is a method of thinking objectively in describing and giving meaning to the real world and has principles to organize and systematize. The indicators of science are: Accumulative, the truth is not absolute, objective. There are six phases of scientific development, including; The PreAncient Greek Phase, the Ancient Greek Phase, the Medieval Phase, the Renaissance Age phase, the Modern Age phase, and finally the Contemporary Age phase.